2015
DOI: 10.1002/aur.1491
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perception of competencies in adolescents with autism spectrum disorders

Abstract: Research has demonstrated that, despite difficulties in multiple domains, children with autism spectrum disorders (ASD) show a lack of awareness of these difficulties. A misunderstanding of poor competencies may make it difficult for individuals to adjust their behaviour in accordance with feedback and may lead to greater impairments over time. This study examined self-perceptions of adolescents with ASD (n = 19) and typically developing (TD) mental-age-matched controls (n = 22) using actual performance on obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…While the AQ parent‐report versions are based on the self‐report AQ for adults, there may be differences in how outside observers rate an individual's autistic traits as compared to how an individual perceives him or herself. Previously, this has been demonstrated both behaviorally [Furlano, Kelley, Hall, & Wilson, ] and using neuroimaging [Lombardo et al, ]. We hypothesized that there would be differences in AQ scores by group according to whether the measure was completed by self‐ or parent‐report.…”
Section: Introductionmentioning
confidence: 93%
“…While the AQ parent‐report versions are based on the self‐report AQ for adults, there may be differences in how outside observers rate an individual's autistic traits as compared to how an individual perceives him or herself. Previously, this has been demonstrated both behaviorally [Furlano, Kelley, Hall, & Wilson, ] and using neuroimaging [Lombardo et al, ]. We hypothesized that there would be differences in AQ scores by group according to whether the measure was completed by self‐ or parent‐report.…”
Section: Introductionmentioning
confidence: 93%
“…The possibility that these types of self-evaluations may be atypical in individuals with ASC has been investigated in two recent studies. Furlano et al (2015) investigated both objective performance and self-evaluated performance of academic tasks in a group of adolescents with ASC and typically developing controls. They found that the ASC group tended to show positively biased self-evaluations, whereas the control group was more accurate.…”
Section: Metacognition In Autism Spectrum Conditionsmentioning
confidence: 99%
“…This is in line with studies focused on explicit measures of self-competence, a concept that correlates highly with self-esteem, in which youth with ASD rated themselves lower on social and athletic competence compared to their TD peers, but not lower on their self-worth (Bauminger et al, 2004; Vickerstaff et al, 2007; Williamson et al, 2008). Furthermore, some individuals with ASD are described to show relatively high levels of grandiosity (Abell & Hare, 2005), showing an overestimation of their competences or self-enhancement of their personality traits (Furlano et al, 2015; Lerner et al, 2012; Locke & Mitchell, 2016). All in all, studies on explicit self-esteem and self-competence in youth with ASD show mixed results, which could be a consequence of difficulties in reporting on their self-esteem.…”
Section: Introductionmentioning
confidence: 99%